Impact of COVID - 19 on practical examination for final year MBBS students in General Medicine - Rikita Ramesh Mudhol; Mohan D. Kashinkunti; Shubashree Mishra (Al Ameen Medical College, 2022)
Background: The COVID -19 pandemic has disturbed the medical education. The pandemic has also made it difficult to assess and conduct examination for the medical students at the end of their academic year. Objective: This study was done to know the impact of COVID - 19 on the changed practical examination pattern. Materials and Methods: This is an observational study which included 100 MBBS students who appeared for final examination in April 2021 in the subject of General Medicine. A pre-validated questionnaire was given to the students which included multiple choice and dichotomous type of questions. The responses were analysed by descriptive statistics. Results: In our study most of the respondents (62%) were of the opinion that the exam conducted was similar to final exam, (34%) felt the exam was conducted in a bettered way and (4%) found it tough. While 95% of the students were of the opinion that they were satisfied with the case scenarios covering all systems and felt that questions asked in the practical examination were relevant. Most of the students (99%) thought that elicitation of clinical signs was better in a case presentation as compared to case scenarios. However 78% students agreed that the Viva - voce was conducted in a bettered way and 22% students disagreed. While 99% of the students agreed that the examination was conducted in the stipulated time. However 93% students preferred clinical case presentation over case scenarios. Conclusion: The COVID-19 pandemic has enabled us to implement new methods of conducting examination. The outcome of present study could help in conducting case scenario - based practical examination for MBBS students in a better way.